The digestive system in mammals food, form, and function - Chivers, David John; Langer, Peter 1942- (Cambridge University Press, 1994)
However well the anatomy of the gastro-intestinal tracts of a wide range of mammals is described and quantified, there can be no real explanation of observed patterns without consideration of the mechanical and chemical properties of the food consumed, and of the digestive stages involved in its processing. This book aims to integrate findings from the many different types of investigations of mammalian digestive systems into a coherent whole. Using the themes of food, form and function, researchers discuss models of digestive processes, linking this with evolutionary aspects of food utilisation. Macroscopic and ultrastructural studies of the gastro-intestinal tract are also presented, as are physiological, ecological and biochemical aspects of the digestion of different food types. The book ends with an integrative chapter, bringing together the themes running through the earlier sections